Yeast Cth2 protein represses the translation of ARE-containing mRNAs in response to iron deficiency - Ramos-Alonso, Lucía (PLoS Genet, 2018)
In response to iron deficiency, the budding yeast Saccharomyces cerevisiae undergoes a metabolic remodeling in order to optimize iron utilization. The tandem zinc finger (TZF)-containing protein Cth2 plays a critical role in this adaptation by binding and promoting the degradation of multiple mRNAs that contain AU-rich elements (AREs). Here, we demonstrate that Cth2 also functions as a translational repressor of its target mRNAs. By complementary approaches, we demonstrate that Cth2 protein inhibits the translation of SDH4, which encodes a subunit of succinate dehydrogenase, and CTH2 mRNAs in response to iron depletion. Both the AREs within SDH4 and CTH2 transcripts, and the Cth2 TZF are essential for translational repression. We show that the role played by Cth2 as a negative translational regulator extends to other mRNA targets such as WTM1, CCP1 and HEM15. A structure-function analysis of Cth2 protein suggests that the Cth2 amino-terminal domain (NTD) is important for both mRNA turnover and translation inhibition, while its carboxy-terminal domain (CTD) only participates in the regulation of translation, but is dispensable for mRNA degradation. Finally, we demonstrate that the Cth2 CTD is physiologically relevant for adaptation to iron deficiency.